Primary Intracranial Choriocarcinoma: MR Imaging Findings - Lv, X.-F.; Qiu, Y.-W.; Zhang, X.-L.; Han, L.-J.; Qiu, S.-J.; Xiong, W.; Wen, G.; Zhang, Y.-Z.; Zhang, J. (American Journal of Neuroradiology, 2010)
SUMMARY: PICCC is the rarest, most malignant primary intracranial GCT. The purpose of this study was to describe and characterize the MR imaging findings in a series of 7 patients (6 males and 1 female; mean age, 11.9 years) with pathologically proved PICCC in our institution from 2004 to 2009. All tumors were located within the pineal (n = 6) or suprasellar (n = 1) regions. On T2-weighted MR imaging, the lesions appeared markedly heterogeneous with areas of both hypointensity and hyperintensity reflecting the histologic heterogeneity, including hemorrhage, fibrosis, cysts, or necrosis. Heterogeneous (n = 7), ringlike (n = 4), and/or intratumoral nodular (n = 3) enhancement was noted on T1-weighted images with gadolinium. These MR imaging findings, combined with patient age and serum β-HCG levels, may prove helpful in distinguishing PICCC from the more common primary brain tumors, thereby avoiding biopsy of this highly vascular tumor. GCTgerm cell tumorHCG/β-HCGhuman chorionic gonadotropin/β-human chorionic gonadotropinPICCCprimary intracranial choriocarcinoma